2016
DOI: 10.1038/srep26334
|View full text |Cite
|
Sign up to set email alerts
|

A method of undifferenced ambiguity resolution for GPS+GLONASS precise point positioning

Abstract: Integer ambiguity resolution is critical for achieving positions of high precision and for shortening the convergence time of precise point positioning (PPP). However, GLONASS adopts the signal processing technology of frequency division multiple access and results in inter-frequency code biases (IFCBs), which are currently difficult to correct. This bias makes the methods proposed for GPS ambiguity fixing unsuitable for GLONASS. To realize undifferenced GLONASS ambiguity fixing, we propose an undifferenced am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Firstly the true ambiguities were obtained by rounding the averaged float value of every continual data arcs of each pair of satellites [ 16 ]. Then, given a threshold of 0.25 [ 27 , 28 ], the WL ambiguity fixing rate is the result of dividing the number of fixed ambiguities by the number of ambiguities.…”
Section: Experimental Analysismentioning
confidence: 99%
“…Firstly the true ambiguities were obtained by rounding the averaged float value of every continual data arcs of each pair of satellites [ 16 ]. Then, given a threshold of 0.25 [ 27 , 28 ], the WL ambiguity fixing rate is the result of dividing the number of fixed ambiguities by the number of ambiguities.…”
Section: Experimental Analysismentioning
confidence: 99%
“…However, this method requires a precise ionospheric model to correct the ionospheric delay. Yi et al (2016) [40] calibrated the odd cycle in the HMW combination for GLONASS wide-lane ambiguity fixing, and found that 96.9% of the GLONASS wide-lane ambiguities can be fixed with a rounding criterion of 0.25 cycles. Liu et al (2018) [41] then calibrated the P1 and P2 IFCBs for GLONASS wide-lane ambiguity fixing and achieved comparable fixing percentages for homogenous and heterogeneous receivers.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2018) [41] then calibrated the P1 and P2 IFCBs for GLONASS wide-lane ambiguity fixing and achieved comparable fixing percentages for homogenous and heterogeneous receivers. While the methods proposed by Yi et al (2016) and Liu et al (2018) can perform GLONASS wide-lane ambiguity fixing directly using the traditional HWM combination, an IFCB calibration table must be established for each individual receiver, which will require considerable calibration work.…”
Section: Introductionmentioning
confidence: 99%